1993
DOI: 10.1093/jn/123.5.964
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nutritional Requirements in Rats: Variation with Time of Weight Gain Responses to Indispensable Amino Acids

Abstract: The Saturation Kinetics Model (SKM) can be used to describe physiological responses as functions of a limiting dietary nutrient. Physiological responses also vary with time, and, by graphing each parameter of the SKM as a function of time, the model equation can be used to produce a three-dimensional response surface, allowing the investigator to predict requirement as a function of both dietary nutrient concentration and time. To test this hypothesis, rats were fed diets containing graded levels of indispensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…It appears that an additional source of variation was in¯uencing the response. A similar problem was observed with another data set (Olivera-Novoa et al 1996). Residual analysis and outlier detection should be performed.…”
Section: Data Qualitysupporting
confidence: 53%
See 3 more Smart Citations
“…It appears that an additional source of variation was in¯uencing the response. A similar problem was observed with another data set (Olivera-Novoa et al 1996). Residual analysis and outlier detection should be performed.…”
Section: Data Qualitysupporting
confidence: 53%
“…A similar failure to test alternative models can be seen in another recently published study (Rodehutscord 1996) Time: A component of nutrition studies that has received little attention is the duration of the experiment. Mercer et al (1993) showed that requirement estimates should be considered a response surface, using dietary nutrient level, weight gain and time as the three dimensions rather than a twodimensional relationship (Fig. 9).…”
Section: Broken Linementioning
confidence: 99%
See 2 more Smart Citations
“…For [57,58], the models used to predict the requirements must have biological and mathematical meaning.…”
Section: Amino Acids Methodologies: Requirementmentioning
confidence: 99%